Application of Finite State Methods in Malayalam Text Analysis - Girija V. R and T. Anuradha (International Journal of Computer Applications, 2017)
This paper discusses the design of a morphological analyzer for Malayalam that can be used for text analysis using Finite State Models. Finite state model that recognizes and strips the morphemes in a string of text are dealt with here.